Perceived Health Benefits of the Banjar Bapukung Tradition for Children: A Qualitative Phenomenological Study in South Kalimantan, Indonesia - Nahdah Nahdah; Novita Ayu Indraswati; Merlin Karinda (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Bapukung is a traditional Banjar infant-care practice in which a baby is wrapped and gently rocked in a cloth swing until calm or asleep. Although the practice remains part of local caregiving culture in South Kalimantan, qualitative evidence on its perceived health benefits for children is still limited. Objective: This study This study aimed to explore community perspectives on the perceived benefits of the Banjar bapukung tradition for children’s health in South Kalimantan, Indonesia. Method: A qualitative study with a phenomenological approach was conducted in Palam Village, South Kalimantan, in 2026. Seventeen informants consisting of mothers, caregivers, and community members with experience or knowledge of bapukung were selected using purposive sampling. Data were collected through in-depth interviews and field observations and analyzed thematically using NVivo. Results: Four major themes emerged: bapukung is perceived to improve children’s sleep quality, calm children and reduce fussiness, strengthen emotional bonding between mother and child, and represent a valuable cultural heritage that should be practiced safely. Participants viewed bapukung as a comforting and practical caregiving method that supports children’s rest and emotional well-being. Conclusion: The Banjar bapukung tradition is perceived to provide positive benefits for children’s comfort, sleep quality, calmness, and emotional well-being, while requiring safe implementation and culturally sensitive health education